The influence of perceived organizational support, compensation, and workload on turnover intention among millennial employees in the sales department of pt. Toyota auto 2000 - Novriananda, Novriananda; Badia Perizade; Kemas Muhammad Husni Thamrin (Jurnal Ekonomi, 2024)
This research aims to examine the influence of perceived organizational support, compensation, and workload on turnover intention at PT. Auto2000. Data collection was carried out by distributing questionnaires to sales employees of PT. Auto2000 Palembang. The population in this study consists of all employees of PT. Auto2000, totaling 175 employees. The sampling technique used is saturated sampling with a total of 75 sales employees of PT. Auto2000 as respondents. Data analysis using multiple linear regression analysis. The results of the analysis in this study indicate that perceived organizational support and compensation have a negative and significant influence on turnover intention, while workload has a positive influence on turnover intention. The researcher suggests that the company should improve compensation for sales employees so that they feel more valued and are less likely to choose turnover. For future research, it is recommended to analyze specifically the causes of turnover in specific departments or positions within an organization.